Synthesis, Characterization, and Applications of ZnO, Ag2O, and ZnO/Ag2O Nanocomposites: A Review - Abel Saka; Leta Tesfaye; Krishnaraj Ramaswamy (Advances in Condensed Matter Physics)
Nanoscale dimensional materials represent a captivating area of research in modern technology, owing to their unique properties and vast potential applications. The distinct advantage of nanosized materials lies in their large surface area to volume ratio, which endows them with enhanced stability and significant functional characteristics. Among these, metal oxide nanomaterials have garnered significant attention due to their substantial energy bandgaps and high exciton binding energies, making them suitable for a wide range of applications, including antimicrobial activity and optoelectronics. This review delves into the synthesis methods of various metal oxides, emphasizing the advantages and drawbacks of physical, chemical, and biological approaches. Specifically, it focuses on the synthesis, characterization, and applications of single metal oxide nanoparticles (NPs), such as zinc oxide (ZnO) and silver oxide (Ag2O), as well as binary or composite metal oxides like ZnO/Ag2O nanocomposites. Through this comprehensive literature review, readers will gain insights into the fabrication techniques and explore the intrinsic properties of both single and composite metal oxide NPs, thereby broadening their understanding of these innovative materials and their potential technological impacts.